A Citical Review of Homeschooling As Alternative Education in Digital Era - Mira Purnamasari Safar (Ijtimā`iyya: Journal of Muslim Society Research, 2018)
Education changes from time to time. In the classical period scientists learn autodidactically with iqra, reading the phenomena observed in the universe. When the era of the industrial revolution happened, education in general are in a schooling system which stiffer and less able to optimize the potential of students, so comes the concept of alternative education that is increasingly in demand and becomes people's choice. One form of alternative education that continues to grow is homeschooling where the flexibility of learning programs is wide enough and homeschooler can study anytime anywhere and with anyone in accordance with their interests, talents and potential. Nowadays homeschooling get recognition from Indonesia ministry department of education and homeschooler are given opportunity to continue their education to higher levels in public or private schools in Indonesia and overseas. Today we are in the digital era. Implementation of homeschooling before and in digital era is certainly different. The digital era like the two opposing sides of a coin, on the one side give a positive influence while on the other side carries a negative influence when it is less wise to use it. This research is a phenomenology research that describes homeschooling as an alternative education and how homeschooling is done in the digital era. The data were obtained through literature study and field study with respondents of homeschoolers in district of Banyumas, Central Java, Indonesia.